2015
DOI: 10.1111/jvh.12467
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of peginterferon alpha‐2b with or without entecavir in patients with HBeAg‐negative chronic hepatitis B: Role of host and viral factors associated with treatment response

Abstract: Combining peginterferon (PEG-IFN) and a potent nucleoside/nucleotide analogue might improve treatment response in patients with chronic hepatitis B (CHB). The aims of this study were to compare the efficacy of PEG-IFN alpha-2b with or without entecavir in HBeAg-negative CHB and to investigate predictors of response. A total of 126 treatment-naïve patients were randomly assigned to receive monotherapy (n = 63) or combination therapy (n = 63) for 48 weeks. Virological response (VR) was defined as HBV DNA level <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
(60 reference statements)
0
28
0
Order By: Relevance
“…As illustrated in Figure , a total of 24 trials were selected from 2632 potentially eligible studies, all of which were published in English . After removal of duplicates and initial screening, 87 studies were further evaluated for eligibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Figure , a total of 24 trials were selected from 2632 potentially eligible studies, all of which were published in English . After removal of duplicates and initial screening, 87 studies were further evaluated for eligibility.…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-three studies were then excluded, for 45 of which did not involve available data, 13 had too small sample sizes, five were focused on occult CHB patients co-infected with HIV. Combination therapies were used in all 24 trials, including IFN combined with LAM in three trials, 37-39 IFN combined with ADV in seven trials, 14,[25][26][27][28][29][30] IFN combined with ETV in six trials, [31][32][33][34][35][36] IFN combined with TDF in two trial 46,47 and IFN combined with at least 2 NAs in seven trials. [40][41][42][43][44][45] Study characteristics are shown in Table 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Out of the 43 studies included, 11‐39 7 were abstracts presented as posters 40‐46 in congresses and 7 full articles were published in Chinese 47‐53 . In 15 studies, patients received antivirals up till enrolment date while in 14 other studies, patients went through 3‐12 months of a washout period before being enrolled.…”
Section: Resultsmentioning
confidence: 99%
“…In this investigator-initiated multicentre global GWA study, CHB patients treated with PegIFN alpha or conventional interferon α (IFN α) within randomized controlled trials, prospective cohort studies, or as part of standard of care at 21 tertiary care centers from Europe, Asia, and North America were initially eligible for inclusion. The inclusion and exclusion criteria for the trials are described elsewhere [7,8,10,[12][13][14][15][16][17][18][19][20][21][22]. For the current study, the minimal duration of therapy was 12 weeks.…”
Section: Patientsmentioning
confidence: 99%